2019
DOI: 10.1177/0748233718814971
|View full text |Cite
|
Sign up to set email alerts
|

Deleterious effects of perinatal exposure to potassium bromate on the development of offspring of Swiss mice

Abstract: The present study aimed to investigate the impact of perinatal potassium bromate (KBrO 3) exposure on the development of sensorimotor reflexes and redox status, and on the histological architecture of the brain, liver, and kidney of newborn mice. Pregnant mice received 1-ml bottled drinking water daily by oral intubation and served as the control group. Another group of pregnant mice were supplemented orally with 200 mg/kg body weight KBrO 3 dissolved in drinking water from gestation day 5 to postnatal day 21.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Previous studies have reported the serious destructive effect of KBrO 3 on different organs such as the kidney [3] , liver [4] , thyroid gland [5] , and the central nervous system [6] . Oxidative DNA damage was also reported as one of the serious effects of bromate [7] and therefore it was considered as a potential carcinogen in both humans and animals [8] and was banned from use in manufactured goods in several countries [9] .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported the serious destructive effect of KBrO 3 on different organs such as the kidney [3] , liver [4] , thyroid gland [5] , and the central nervous system [6] . Oxidative DNA damage was also reported as one of the serious effects of bromate [7] and therefore it was considered as a potential carcinogen in both humans and animals [8] and was banned from use in manufactured goods in several countries [9] .…”
Section: Introductionmentioning
confidence: 99%